157k views
3 votes
2x2 + 3x = -1 using the quadratic formula

2 Answers

3 votes


{2x}^(2) + 3x = - 1
add 1 to both sides

{2x}^(2) + 3x + 1 = 0
plug in for the formula

{ax}^(2) + bx + c

\frac{ - b + ( - ) \sqrt{ {b}^(2) - 4(a)(c) } }{2(a)}

\frac{ - 3 + ( - ) \sqrt{ {3}^(2) - 4(2)(1) }}{2(2)}
simplify by multiplying and exponents


( - 3 + ( - ) √( 9 - 8 ))/(4)
subtract then solve the square root


( - 3 + ( - ) √( 1))/(4)

( - 3 + ( - ) 1)/(4)
now solve for the plus and minus
(plus):

( - 3 + 1)/(4)

( - 2)/(4) = - 0.5
(minus):

( - 3 - 1)/(4)

( - 4)/(4) = - 1
so the answer would be -0.5 and -1
User Jason Stallings
by
5.7k points
0 votes
a = 2
b = 3
c = 1

x = [(-b +-sq root (b^2 -4ac)] / 2a
x = [-3 +- sq root (9 - 8) ] / 4
x1= (-3 + 1) / 4 = -.5

x2 = (-3 - 1) / 4 = -1



User Bzx
by
5.9k points